Please help me with this question

Asked by  | 19th Apr, 2010, 10:05: AM

Expert Answer:

Using the following result,we can write,

tan(C+D) = (tanC + tanD)/(1 - tanC tanD)

tan2A = [tan(A+B) + tan(A-B)]/(1 - tantan(A+B) tan(A-B)) = (x+y)/(1 - xy)

Similarly,

tan2B = [tan(A+B) - tan(A-B)]/(1 + tan(A+B) tan(A-B)) = (x-y)/(1 + xy)

Regards,

Team,

TopperLearning.

Answered by  | 19th Apr, 2010, 01:53: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.